Little Mouse's big book of fears - Gravett, Emily (Simon & Schuster Books for Young Readers, 2008)
Little Mouse draws pictures of some of the many things he is afraid of, including creepy crawlies, sharp knives, and having accidents, and provides the correct scientific name for each of his fears.